An infant‐led approach to complementary feeding is positively associated with language development - Charlotte Webber; Jacqueline Blissett; Elsa Addessi; Amy T. Galloway; Laura Shapiro; Claire Farrow (Wiley, 2021)
Abstract The timing and strategy with which parents first introduce their infants to solid foods may be an important predictor of subsequent developmental outcomes. Recent years have seen a decline in the prevalence of traditional parent‐led feeding of soft, puréed food and a rise in the prevalence of infant‐led complementary feeding. Although there has been some research espousing the benefits of infant‐led complementary feeding for improving food fussiness and self‐regulation, there has been little exploration of this approach that may impact on other developmental outcomes in children. The current study explores whether aspects of the infant‐led approach, specifically the child eating unaided and consuming finger foods and eating with the family, are related to child language outcomes. One hundred thirty one parents of children aged 8-24 months completed questionnaires about their approach to complementary feeding, their current feeding practices, their child's experiences with family foods and child language comprehension/production. The findings suggest that an approach to complementary feeding which promotes infant autonomy in feeding (i.e., eating finger foods rather than puréed foods) and consuming more family foods is related to more advanced child language production and comprehension. Specifically, the prevalence of eating family foods mediated the relationship between eating unaided at the onset of the complementary feeding period and later language outcomes. This study is the first to find a significant relationship between different approaches to introducing solid foods and child language outcomes and these findings highlight the potential for different complementary feeding approaches to influence behaviour beyond mealtimes.